2007
DOI: 10.1186/1745-6150-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundThe timing of the origin of introns is of crucial importance for an understanding of early genome architecture. The Exon theory of genes proposed a role for introns in the formation of multi-exon proteins by exon shuffling and predicts the presence of conserved splice sites in ancient genes. In this study, large-scale analysis of potential conserved splice sites was performed using an intron-exon database (ExInt) derived from GenBank.ResultsA set of conserved intron positions was found by matching id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…These results agree with those previously reported showing that introns with phase 0 were normally located in more conserved portions of genes than introns with phases 1 or 2 [36]. Previous studies demonstrated that conserved intron positions were found within a variety of ancient protein modules, suggesting that the initial function of exons did not represent the boundaries of functional protein modules, but that the domain itself was assembled from exons [37]. These results suggest that the phases of introns and the numbers of the VHA-H genes were well-conserved and that some introns (i.e., those located in the middle portion of the N-terminal domain) maintained their specificity.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with those previously reported showing that introns with phase 0 were normally located in more conserved portions of genes than introns with phases 1 or 2 [36]. Previous studies demonstrated that conserved intron positions were found within a variety of ancient protein modules, suggesting that the initial function of exons did not represent the boundaries of functional protein modules, but that the domain itself was assembled from exons [37]. These results suggest that the phases of introns and the numbers of the VHA-H genes were well-conserved and that some introns (i.e., those located in the middle portion of the N-terminal domain) maintained their specificity.…”
Section: Discussionsupporting
confidence: 92%
“…The addition of genetic polymorphism thus serves as a mechanism by which variation was reintroduced and phenotypic robustness restored over subsequent generations. Other work has shown that robustness to mutations in the P450 protein was higher in larger and more polymorphic populations compared to smaller and less polymorphic populations such that genetic polymorphism is likely responsible for higher robustness 46 . It was further revealed that the genetic background in which the HSP90 chaperone is expressed can have a large effect on resultant phenotypes, as is the case in Drosophila 47 .…”
Section: Discussionmentioning
confidence: 97%
“…One can see that the red rectangular boxes that represent the SCP2 domains are found in all 14 protein hits. Additional domains seen in the protein hits are: (1) Band_7 (violet box)—an integral membrane protein involved in regulation of cation conductance; (2) adh_short (brown box)—an NAD or NADP-dependent oxidoreductase domain; (3) MaoC_dehydratas (blue box)—a domain involved in the synthesis of monamine oxidase; (4) Thiolase_N (green box) and (5) Thiolase_C (gray box) domains are both involved in degradative pathways such as fatty acid beta-oxidation.
Figure 3.Results of the sample query for the protein domain ‘ SCP2’ in ExDom.
…”
Section: Exploring the Utility Of The Database With A Sample Querymentioning
confidence: 99%